Factors Affecting The Repayment Rate of Musharaka Financing On Micro Enterprises ; Case Study of BMT Al Munawwarah, South Tangerang - Jaenal Effendi; Anggita Aulia Pratiwi (AHKAM : Jurnal Ilmu Syariah, 2017)
The existence of micro-enterprises has an important role in nationa leconomy. However, access to financial institutions for obtaining additional capital for their business is still low. It has influenced the characteristics ofmicro-enterprises considered to be not bankable. The purpose of this study isto analyze the characteristics of the micro-enterprises based on the repay mentrate of musharaka financing and analyze the factors affecting repaymentrate of musharaka financing, which given to micro-enterprises at BMT Al Munawwarah, South Tangerang. By a logit method,this research showed a significant variable affecting repayment rate of musharaka financing namely gender, the amount of financing, collateral, other loans, and BMT visitation. DOI: 10.15408/ajis.v17i2.6238